2018
DOI: 10.1080/10807039.2018.1436435
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and contamination assessment of arsenic and mercury in surface sediments from the intertidal zone of Yantai Sishili Bay, China

Abstract: Sixty surface sediment samples from the intertidal zone of Yantai Sishili Bay (YSB) have been analyzed for arsenic (As) and mercury (Hg) to evaluate their contamination levels and potential ecological risks. Concentrations of As and Hg ranged from 7.01-23.56 and 0.00-0.01 mg g ¡1 in the dry season; during the wet season, the corresponding data were 1.44-6.17 and 0.00-0.02 mg g ¡1. The geoaccumulation index (I geo) and potential ecological risk index (E r i) were used to conduct a pollution assessment. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Compared with previous studies, the observed concentrations of Fe carb (0.129–0.973 g kg −1 ) in sediments in Lake Xiaoxingkai and Lake Xingkai were much higher than those in the Yellow River (0.01–0.07 g kg −1 ) [45] , Swan Lagoon (∼0.1 g kg −1 ) [46] , and Yantai Sishili Bay (0–0.0044 g kg −1 ) [47] , perhaps due to their different inner biogeochemical conditions and geographic positions. Fe carb is mainly adsorbed on the surface of fine CaCO 3 in sediments [48] , and thus Fe carb concentrations are possibly related to CaCO 3 deposition.…”
Section: Discussioncontrasting
confidence: 76%
“…Compared with previous studies, the observed concentrations of Fe carb (0.129–0.973 g kg −1 ) in sediments in Lake Xiaoxingkai and Lake Xingkai were much higher than those in the Yellow River (0.01–0.07 g kg −1 ) [45] , Swan Lagoon (∼0.1 g kg −1 ) [46] , and Yantai Sishili Bay (0–0.0044 g kg −1 ) [47] , perhaps due to their different inner biogeochemical conditions and geographic positions. Fe carb is mainly adsorbed on the surface of fine CaCO 3 in sediments [48] , and thus Fe carb concentrations are possibly related to CaCO 3 deposition.…”
Section: Discussioncontrasting
confidence: 76%
“…DO, Chl a, and S distribution were shown in Figure S2. The water temperature was high (T = 25.27 ± 0.81°C) (Table S2) and reached the optimum temperature for the growth of most phytoplankton (Wang et al, 2018a). The salinity (S = 31.05 ± 0.20 ‰) and pH value (7.93 ± 0.15) only varied to a limited extent (Table S2 and Figure S2).…”
Section: Investigation Of Hydrological Parameters and Dissolved Carbo...mentioning
confidence: 99%